2018
DOI: 10.3389/fimmu.2018.02605
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR in Cytotoxic T Lymphocytes Predicts Breast Cancer Patients' Response to Neoadjuvant Chemotherapy

Abstract: Prediction of breast cancer response to Neoadjuvant Chemotherapy (NACT) is an urgent need to promptly direct non-responder patients to alternative therapies. Infiltrating T lymphocytes, namely cytotoxic T lymphocytes (CTLs) have been appointed as predictors of response. However, cancer cells have the ability to dampen CTLs' activity and thus, the prognostic value of the CTLs, per se, is debatable. Here, we disclose that more than the occurrence of CTLs, it is their activation state, revealed by HLA-DR expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 43 publications
8
75
1
1
Order By: Relevance
“…Interestingly, some our patients on novel agents had a very low HLA-DR expression on immune cells. Since HLA-DR expression on immune cells may re ect the response to the therapy as shown in breast cancer patients [28], our patients on novel drugs with low immune cell activation may have a high risk of disease progression, as shown in some cases. Interestingly, our data showed different time-dependent dynamics of immune cell activation and redistribution of CLL cells from tissues to peripheral blood when treated with ibrutinib and idelalisib, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, some our patients on novel agents had a very low HLA-DR expression on immune cells. Since HLA-DR expression on immune cells may re ect the response to the therapy as shown in breast cancer patients [28], our patients on novel drugs with low immune cell activation may have a high risk of disease progression, as shown in some cases. Interestingly, our data showed different time-dependent dynamics of immune cell activation and redistribution of CLL cells from tissues to peripheral blood when treated with ibrutinib and idelalisib, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, HLA-DR expression on leukemic cells was suggested to be essential for establishing effective antitumor immunity via CD4 + cell activation and the recruitment of effector cell populations, such as macrophages [27]. Besides being an important prognostic marker on tumor cells, HLA-DR expression on immune cells has been shown to re ect the tumor immune status and the response to the therapy [28]. In line with the above evidence, we suggested that HLA-DR expression may re ect disease progression and the treatment response in CLL as well.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DR, as a T lymphocyte immune-regulatory molecule has been shown to vary during the cancer progression [28]. Saraiva et al, demonstrated that HLA-DR + expression signi cantly declined in cancer subjects and is strongly connected with prognosis [29][30], as reported in 67% of gastric cancer cases and in 80% of poorly differentiated adenocarcinoma [31]. Intriguingly, our study showed that HLA-DR co-expression in CD3, CD4 and CD8 subsets was a signi cant trend towards suppression of drug stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some our patients on novel agents had a very low HLA-DR expression on immune cells. Since HLA-DR expression on immune cells may reflect the response to the therapy as shown in breast cancer patients [28], our patients on novel drugs with low immune cell activation may have a high risk of disease progression, as shown in some cases. Interestingly, our data showed different time-dependent dynamics of immune cell activation and redistribution of CLL cells from tissues to peripheral blood when treated with ibrutinib and idelalisib, respectively.…”
Section: Hla-dr Expression On Monocyte Subpopulations Does Not Differmentioning
confidence: 93%
“…Moreover, HLA-DR expression on leukemic cells was suggested to be essential for establishing effective antitumor immunity via CD4+ cell activation and the recruitment of effector cell populations, such as macrophages [27]. Besides being an important prognostic marker on tumor cells, HLA-DR expression on immune cells has been shown to reflect the tumor immune status and the response to the therapy [28]. In line with the above evidence, we suggested that HLA-DR expression may reflect disease progression and the treatment response in CLL as well.…”
Section: Hla-dr Expression On Monocyte Subpopulations Does Not Differmentioning
confidence: 99%